WORKLOAD AND RESPONSE İN PREHOSPİTAL EMERGENCY HEALTH SERVİCES: WORKLOAD AND RESPONSE İN PREHOSPİTAL EMERGENCY HEALTH SERVİCES - Duran, Metehan; Tahta, Yahya; ŞAHİNGÖZ TAHTA, Mehtap (Halo 194 Scientific Journal of Emergency Medicine, 2024)
Background: In emergency situations, it is very important to prevent preventable losses, to get early information, reaching the scene in a short time as well as providing intervention by equipped and trained personnel.This study was conducted to investigate the cases in prehospital Emergency Health Services. Methods:In this retrospective study, 75.280 cases who applied to Kayseri 112 Emergency Health Services with the phone number of 112 were examined. The data include the demographic characteristics of the cases, the hospital where the cases are referred, the reason for the call, the diagnosis, the ambulance exit result, the arrival time of the case, the source of the call, etc. collected with a form containing the questions. In the data analysis, descriptive statistical methods were used. Results: It was determined that the emergency calls were mostly made between 10:00-16:00 and 57.3% of the transfers were mostly made to the Training and Research Hospital. Internal medicine problems were the top reason for the calls. According to the ambulance exit results, 66.7% of the cases resulted in transfer to the hospital. Conclusions:It is seen that the number of cases making an emergency call for emergency health services is increasing day by day. It was found that the highest number of application were made by the male gender and the demand was higher during the daytime. In the present study, more than half of the cases were not accepted as emergency according to the international emergency parameters determined by the World Health Organization (WHO).